Plasma concentrations of amino acid and nicotinamide metabolites in rheumatoid arthritis – potential biomarkers of disease activity and drug treatment. (2nd April 2016) - Smolenska, Zaneta; Smolenski, Ryszard T.; Zdrojewski, Zbigniew
Abstract: This study aimed to evaluate changes in plasma amino acid and nicotinamide metabolites concentrations in rheumatoid arthritis (RA) in a search for potential biomarkers of the disease activity and the effect treatment. Analysis of plasma metabolite patterns with liquid chromatography/mass spectrometry revealed specific changes in RA as well as correlations with clinical parameters. Combined concentration parameter calculated as [aspartic acid] + [threonine] + [tryptophan] − [histidine] − [phenylalanine] offered the strongest correlation ( p  < 0.001) with pain joint count, swollen joint count and DAS 28. Such analysis of amino acid and related metabolite pattern offers potential for diagnosis as well as for monitoring disease progression and therapy in RA.